2006
DOI: 10.1159/000094906
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase Plasminogen Activator in Injured Adventitia Increases the Number of Myofibroblasts and Augments Early Proliferation

Abstract: Myofibroblasts are involved in vessel remodeling during the development of hypertension as well as after angioplasty and aortocoronary grafting, but the mechanisms of myofibroblastic phenotypic modulation are not fully elucidated. We assessed the role of urokinase plasminogen activator (uPA) and its proteolytic activity in myofibroblast differentiation and the early proliferation following mechanical injury of the rat carotid adventitia. The effects of perivascular application of recombinant uPA (r-uPA), prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 80 publications
0
8
1
2
Order By: Relevance
“…Previous studies demonstrated the expression of MMPs and uPA in both neoplastic and stromal components of ameloblastomas, permitting the hypothesis that these matrixdegrading enzymes may contribute to the local invasiveness of this odontogenic tumor [22][23][24][25]. Since recent reports have demonstrated that identification of myofibroblast have a prognostic role in many neoplasm [2,12,26,27] and that those cells produce high levels of MMP-2 and uPA [2,4,[14][15][16][17][18][19][20], the aim of the present study was to analyze the presence of myofibroblasts and the expression of MMP-2 and uPA in intra-osseous solid multicystic ameloblastoma to establish their prognostic significance.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies demonstrated the expression of MMPs and uPA in both neoplastic and stromal components of ameloblastomas, permitting the hypothesis that these matrixdegrading enzymes may contribute to the local invasiveness of this odontogenic tumor [22][23][24][25]. Since recent reports have demonstrated that identification of myofibroblast have a prognostic role in many neoplasm [2,12,26,27] and that those cells produce high levels of MMP-2 and uPA [2,4,[14][15][16][17][18][19][20], the aim of the present study was to analyze the presence of myofibroblasts and the expression of MMP-2 and uPA in intra-osseous solid multicystic ameloblastoma to establish their prognostic significance.…”
Section: Introductionmentioning
confidence: 94%
“…Through expression and secretion of cytokines, chemokines, growth factors, extracellular matrix molecules, adhesion molecules and receptors, myofibroblasts promote epithelial-mesenchymal interactions, including neoplastic growth and invasion [4,[8][9][10][11][12][13]. Myofibroblasts also secrete enzymes responsible for matrix remodeling, including matrix metalloproteinase-2 (MMP-2) [4,[14][15][16] and urokinase plasminogen activator (uPA) [2,[17][18][19][20]. In addition, activation of those enzymes can lead to release and activation of sequestered cytokines and growth factors, which may favor angiogenesis and promotion of cellular migration [4].…”
Section: Introductionmentioning
confidence: 99%
“…5a). Northern blot analyses were performed to investigate the effects of uPA-nAChR␣1/ uPAR interactions on fibroblast ␣SMA expression, a cytoskeleton protein marker for "activated" fibroblasts or myofibroblast phenotypic transformation (41,42) (Fig. 5b).…”
Section: Renal Expression Of Nachr␣1 and Acetylcholine Duringmentioning
confidence: 99%
“…Ассоциация uPar с α5β1 индуцирует в интегрине появление дополни-тельного сайта для фибронектина в дополне-ние к связывающему rgd-сайту. недавно на uPar был идентифицирован сайт связывания с α5β1 во втором домене (130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142) [49].…”
Section: сигнализация урокиназыunclassified
“…Способность урокиназы вызывать констриктивное ремоде-лирование поврежденной артерии может быть обусловлена ее влиянием на адвентицию сосу-да. нанесение на адвентицию экзогенной уро-киназы стимулирует ее рост, пролиферацию клеток и аккумуляцию α-актинположительных клеток и моноцитарно-макрофагальную ин-фильтрацию, а нейтрализующие урокиназу антитела, напротив, уменьшают количество клеток сок ратительного фенотипа и подавляют рост неоадвентиции в ответ на повреждение [142]. при этом, неактивная урокиназа (uPah/Q) и тканевой активатор плазминогена не оказывают стимулирующего влияния на ак-кумуляцию α-актинположительных клеток и макрофагов в поврежденной адвентиции, что указывает на определяющее значение протео-литической активности урокиназы для осу-ществления этих процессов.…”
Section: рис 8 схема механизмов способствующих пролиферации клетокunclassified